Implementasi Pendekatan Deep Learning Melalui Kegiatan Eksplorasi Untuk Berpikir Kritis Anak Usia Dini TK Golden Kids Sentosa Palembang - Melinda Puspita Sari Jaya; Puteri Amrina Rosada; Marwiyah Marwiyah; Kurniati Kurniati; Wahyu Triastuti; Nabila Azhari; Rosita Watri; Tria Meinanda (Universitas Pakuan, 2026)
IMPLEMENTING THE DEEP LEARNING APPROACH THROUGH EXPLORATION ACTIVITIES TO FOSTER CHILDREN'S CRITICAL THINKING AT TK GOLDEN KIDS SENTOSA PALEMBANG Critical thinking skills need to be stimulated from an early age so children can observe, ask questions, and draw simple conclusions from their learning experiences. This article describes the implementation of the Deep Learning approach through exploration activities to stimulate the critical thinking skills of Group B1 children at TK Golden Kids Sentosa Palembang. The activities were carried out through an 11-week School Field Introduction Program (PLP) covering observation, teaching assistance, and independent teaching practice involving 28 children. A qualitative descriptive approach was used, with data collected through participatory observation, documentation, and field notes across six learning sessions themed Universe and Communication Tools. The results show that implementing the Deep Learning approach through exploration and simple experiments—such as observing the moon and stars, a volcanic-eruption experiment, rainbow bubbles, a lightning simulation, and making a cardboard telephone—encouraged children to be more active in observing, asking questions, expressing opinions, making predictions, comparing objects, and drawing simple conclusions. This development occurred gradually, although the level of critical thinking varied among children. Supporting factors included guidance from the cooperating teacher and supervising lecturer, adequate facilities, and children's enthusiasm, while inhibiting factors related to differences in children's characteristics, limited time, and the writer's limited teaching experience. It is concluded that the Deep Learning approach through exploration activities contributes positively to the development of early childhood critical thinking skills.